The Genetics of Leber’s Hereditary Optic Neuropathy: A Literature Review - Henry Liu (University of Ottawa Journal of Medicine, 2018)
Leber’s hereditary optic neuropathy (LHON) is a mitochondrial disease characterized by a painless, acute loss of central vision, with 95% of affected individuals harbouring one of three pathogenic mutations (G11778GA, G3460A, or T14484C). The purpose of this review is to highlight the distinguishing clinical presentations of the disease with respect to the mutation subtype and present our recent understanding of two unique features of the disease: male predominance and incomplete penetrance. We also review recent advancements made in the diagnosis and treatment of this rare mitochondrial disease and their implications for genetic counselling.